Effect of the fertilizationwith diverse sources on the yield of cacao (Theobroma cacao L.) - Ruales Mora, José Luis; Burbano Orjuela, Hernán; Ballesteros Possú, William (Revista de Ciencias Agrícolas, 2011)
Nutrition is an alternative to increase yields in the cocoa crop (Theobroma cacao L.). For this reason the aim of this study was to assess three levels of fertilization. Treatment 1 (500 grams/tree/year Yaramila Hydran (19-4-19-3 (MgO) -1.8 (S) -0.1 (B) -0.1 (Zn)), 350 grams/tree/year Nitrabor (15,5-0-0 26 (CaO) -0.3 (B), 250 grams/tree/year KMag (0-0- 22-18 (MgO) -22 (S) and 50 grams/tree/year of granular KCl). Treatment 2 (250 grams/ tree/year Yaramila Hydran (19-4-19-3 (MgO) -1.8 (S) -0.1 (B) -0 , 1 (Zn)), 175 grams/ tree/year Nitrabor (15,5-0-0-26 (CaO) -0.3 (B), 125 grams/tree/year KMag (0-0-22-18 (MgO) -22 (S) and 25 grams/tree/year of granular KCl); these treatments were split every 4 months to improve the assimilation of nutrients by plants. Treatment 3 (300 grams/ tree/year humic acid and 100 grams/tree/years sulfoma (K 26%, Mg 11% S 20%), The cocoa performance was evaluated in five materials (hybrid, CCN-51, TSH-565, CAP- 34, ICS-60); the trial was conducted in La Granja Luker located in Palestina, Caldas. There were significant differences between doses of the treatments, the best results were treatment 1; Tested materials often reacted differently to the application of fertilizers, hybrid being the most responsive in interaction with treatment 1, for some materials there was significant difference in the case of clone ICS - 60. Treatment 3 gave the lowest scores in performance, the need for fertilization of this crop became evident.